Economic impact of fluctuations in oilsardine landings in India - Aswathy, N.; Narayanakumar, R.; Salim, Shyam S.; Rohit, Prathibha; Gopalakrishnan, A. (Indian Journal of Fisheries, 2020)
The Indian oilsardine Sardinella longiceps (Valenciennes, 1847) is a significant contributor to the marine fisheries economy of India. The species showed wide fluctuations in landings in the past and during recent years, the decline in landings is an issue of concern for sustainable harvest of the resource especially in the context of climate change regime. The paper analysed the economic impacts of fluctuations in oilsardine landings in terms of gross earnings realised at landing centre and retail levels; inflation in the domestic markets and external trade during the 2000-2018 period. The analysis indicated that the decline in landings was more in the state of Kerala as compared to all India landings. The inflation at point of first sales (landing centre level) was more during 2000-09 period whereas at retail market level  inflation was  highest during 2010-2018. The inflationary pressure on domestic consumers in Kerala was more during 2010-2018 period. The growth in external trade of sardines was in tune with the Indian oilsardine landings in the country.Keywords:  External trade, Fluctuations, Growth, Indian oilsardine, Inflation, Instability